WORLD OF TOMORROW. - Bradshaw, Nick (Sight & Sound)
This article focuses on Texan independent animator Don Hertzfeldt’s transition from analogue to digital animation through his sci-fi trilogy *World of Tomorrow*, which explores themes of identity, memory, and time via stick-figure clones navigating complex timelines. The trilogy, consisting of three episodes released between 2015 and 2020, employs digital tools to create rich, multifaceted visuals while retaining Hertzfeldt’s signature hand-drawn aesthetic and existential humor. Hertzfeldt discusses his creative process, emphasizing a non-linear, iterative approach to storytelling and his efforts to maintain logical coherence in the films’ intricate time-travel narratives. The article also highlights Hertzfeldt’s use of his niece’s child voice acting and his incorporation of musical and cinematic references, such as theremin-based scores inspired by classic science fiction films.